The Geology of Southern Africa - Skinner, Brian J., 1928-; Educational Media International (Haymarket, Va. : Educational Media International, 1982)
An overview of the principal tectonic units and the geologic development of the southern third of Africa.
Keywords: Geology -- Africa, Southern